Redefining state sovereignty: The complexities of Humanitarian intervention and the Responsibility to Protect - Ofuani, Suzzie Onyeka (Department of Public Law, 2014)
At the time this statement was made by the former Secretary General of the United Nations, the international community was engulfed in a debate concerning humanitarian intervention and its effect on state sovereignty. Recent interventions in states such as East Timor, Haiti and Kosovo had sparked off concern regarding the tension between sovereignty and the recognition of human rights norms which has for a long time 'raged' within academic institutions and the international community as a whole. In the rhetoric of international politics, attempts to establish the responsibility of states to respect human rights within their jurisdictions are often countered with claims of sovereign equality and the principle of non-intervention.